Constructing the “New” Arctic: The Future of the Circumpolar North in a Changing Global Order - O. R. Young (Контуры глобальных трансформаций: политика, экономика, право, 2019)
Like all spatially delimited regions in international society, the Arctic is socially constructed. Political and economic considerations play prominent roles as determinants of the region’s boundaries, the identity of those states regarded as Arctic states, and the nature of the interactions between the Arctic and the outside world. From this perspective the recent history of the Arctic divides into two distinct periods: the late 1980s through 2007 and 2007 to the present. As the cold war faded, the Arctic became a peripheral region of declining importance in global political calculations. No one challenged the dominance of the eight Arctic states in regional affairs, and the Arctic Council focused on regional concerns relating to environmental protection and sus tainable development. Today, by contrast, the ‘new’ Arctic is a focus of intense glo bal interest, largely because climate change is proceeding more rapidly in this region than anywhere else on Earth with global consequences and because the increasing accessibility of the Arctic’s natural resources has generated enhanced interest on the part of outside actors. As a result, Arctic issues have merged into global issues, making the region a prominent arena for the interplay of geopolitical forces. Cooperative arrangements established during the first period (e.g. the Arctic Council) may require adjustment to operate effectively in the ‘new’ Arctic. Treated as a case study, the Arctic story provides an illuminating lens through which to analyze the forces that shape thinking about the nature of regions in international society and the role of cooperative arrangements at the regional level.